2006
DOI: 10.1897/05-356r.1
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of lead on northern leopard frog (Rana pipiens) tadpoles

Abstract: Northern leopard frogs (Rana pipiens) were exposed to environmentally relevant concentrations of lead in water (3, 10, and 100 microg/L as lead nitrate) from the embryonic stage to metamorphosis. Survival, growth, deformity, swimming ability, metamorphosis, and lead tissue concentrations were evaluated. Tadpole growth was significantly slower in the early stages (Gosner stages 25-30) in 100 microg/L treatment. More than 90% of tadpoles in the 100 microg/L treatment developed lateral spinal curvature, whereas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Delayed neurobehavioral changes have already been reported in rats exposed to As (III) (Rodriguez et al 2002). Maximum swimming speed has been shown to be a sensitive behavioral endpoint of metal toxicity in tadpoles (Jung and Jagoe 1995;Chen et al 2006Chen et al , 2007. Although not fatal in the controlled laboratory environment, decreased sprint swim speed may cause tadpoles to be more susceptible to predation where predators exist (Raimondo et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed neurobehavioral changes have already been reported in rats exposed to As (III) (Rodriguez et al 2002). Maximum swimming speed has been shown to be a sensitive behavioral endpoint of metal toxicity in tadpoles (Jung and Jagoe 1995;Chen et al 2006Chen et al , 2007. Although not fatal in the controlled laboratory environment, decreased sprint swim speed may cause tadpoles to be more susceptible to predation where predators exist (Raimondo et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Maximum swimming speed of tadpoles, an index of predator avoidance ability, was also measured on d 44 following the methods described in our previous study (Chen et al 2006). Ten tadpoles were randomly selected from each tank.…”
Section: Toxicity Testmentioning
confidence: 99%
“…However, the lack of effect of heavy metal exposure contradicts the conclusions of past studies (Linder and Grillitsch 2000), although this may be due to the small sample size and low statistical power incurring in type II errors. Moreover, the reported study revealed that the lack of effect of heavy metals on survival may be mediated by the elevated mortality in control treatment (Chen et al 2006), also increasing type II errors. Further research is needed to verify the effects of heavy metals on amphibian survival.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic activity of d-aminolevulinic acid dehydratase, a heme biosynthesis enzyme, was inhibited in fish at highly Pb-contaminated sites [15]. Furthermore, exposure to Pb resulted in a slower growth rate and spinal deformity in northern leopard frog (Rana pipiens) [16]. In recent years a national upward trend of Hg in the environment has been identified [17].…”
Section: Introductionmentioning
confidence: 99%